2015
DOI: 10.1007/s10815-015-0430-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-carnitine supplementation on maturation and early embryo development of immature mouse oocytes selected by brilliant cresyle blue staining

Abstract: These data indicated that L-carnitine supplementation during IVM of immature BCB+ oocytes improved preimplantation developmental competence of oocytes after IVF, probably by accelerating cytoplasmic and nuclear maturation of oocytes. It may provide a novel approach to improving ART outcomes in infertile couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 54 publications
(62 reference statements)
5
24
0
3
Order By: Relevance
“…In the present study, treatment of culture medium with TQ was shown to reduce ROS generation and enhance GSH production (Figure ), which, in turn, had profound effects on the fertilization rate. Such results have previously been shown with L‐carnitine, melatonin, resveratrol and cysteine supplementation in culture media (De Matos & Furnus, ; Nikmard et al, ; Wang et al, ; Zare et al, ). It has also been shown that TQ could reduce oxidative stress levels via its modulatory role on NF‐κb signaling (Arif et al, ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the present study, treatment of culture medium with TQ was shown to reduce ROS generation and enhance GSH production (Figure ), which, in turn, had profound effects on the fertilization rate. Such results have previously been shown with L‐carnitine, melatonin, resveratrol and cysteine supplementation in culture media (De Matos & Furnus, ; Nikmard et al, ; Wang et al, ; Zare et al, ). It has also been shown that TQ could reduce oxidative stress levels via its modulatory role on NF‐κb signaling (Arif et al, ).…”
Section: Discussionsupporting
confidence: 75%
“…results are indicating that the treatment of culture medium with 10 μM-TQ does not change the cyclin B expression, but it significantly increases transcription levels of Mapk and Cdk1 genes which result to an increase of polar body extrusion in treated oocytes. These observations are consistent with previous findings, that the upregulation of Cdk1 transcript levels during IVM supplementation with L-carnitine significantly improved MPF activity at MII stage oocytes(Zare et al, 2015).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Thus, l-Cn, whose role is to deliver long-chain fatty acids to mitochondria for catabolism, was shown to decrease LB in the cells, which indirectly could indicate an increase in the energetic status of the cells. Indeed, it has been suggested that l-Cn ameliorates maturation of mouse oocytes and early embryo development (Zare et al 2015), while decreasing DNA damage and improving the in vitro blastocyst development rate in mouse embryos (Abdelrazik et al 2009). It could, therefore, be hypothesized that in the presence of l-Cn, zygotes with limited energetic reserves could not proceed to development and thus only healthy embryos could reach the stage of 2-cells.…”
Section: Discussionmentioning
confidence: 99%